Emotional Intelligence: What Is It and How Can It Transform Your Life? - Harpreet Singh Dhillon; Shibu Sasidharan; Gurpreet Kaur Dhillon; Babitha Manalikuzhiyil (Indian Journal of Psychiatric Nursing)
Emotional intelligence (EI) is a social intelligence distinct from academic intelligence and assists us in successfully comprehending complex personal, social, and professional situations. The four components of EI are perceiving, understanding, managing, and using emotions to enable better adaptability and creativity. In this review, the authors have examined the existing literature on the contemporary concepts of EI construct, the available means to measure it, and its implications across various life situations with special emphasis on the lockdown due to the COVID-19 pandemic. The necessity for research into multiple intelligences (cultural, practical, and spiritual) is further discussed in the way forward.